Identities for the Widder transform and transforms with Bessel function kernels - UÇAR, FARUK (ELSEVIER SCIENCE INC, 2011)
In the present paper, we consider the classical Widder transform, the H(v)-transform, the K(v)-transform, and the Y(v)-transform. Some identities involving these transforms and many others are given. By making use of these identities, a number of new Parseval-Goldstein type identities are obtained for these and other well-known integral transforms. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Laplace transforms; Widder potential transforms; H(v)-transforms; K(v)-transforms; Y(v)-transforms; Parseval-Goldstein type theorems